THE IDEAS OF FORMING METHODOLOGICAL PRINCIPLES OF RATIONAL-ECOLOGICAL SOCIETY DEVELOPMENT IN ORIGINAL LEGACY V.I. VERNADSKY - Chornomordenko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article analyzed the legacy of Vernadsky, in particular the concept of "noosphere" and the concept of "living matter" in terms of their possible use as a basis in forming methodological foundations of rational-ecological attitude between scientists, that may arise in the form of interdisciplinary scientific relations. Such research through links to ecological rationality, giving scientists an opportunity globally realize and change academic instruction, guidance and strategies for solving environmental problems.